Predation threats for a 24-h period activated the extension of axons in the brains of Xenopus tadpoles - Tsukasa Mori (Nature Portfolio, 2020)
Abstract The threat of predation is a driving force in the evolution of animals. We have previously reported that Xenopus laevis enhanced their tail muscles and increased their swimming speeds in the presence of Japanese larval salamander predators. Herein, we investigated the induced gene expression changes in the brains of tadpoles under the threat of predation using 3′-tag digital gene expression profiling. We found that many muscle genes were expressed after 24 h of exposure to predation. Ingenuity pathway analysis further showed that after 24 h of a predation threat, various signal transduction genes were stimulated, such as those affecting the actin cytoskeleton and CREB pathways, and that these might increase microtubule dynamics, axonogenesis, cognition, and memory. To verify the increase in microtubule dynamics, DiI was inserted through the tadpole nostrils. Extension of the axons was clearly observed from the nostril to the diencephalon and was significantly increased (P ≤ 0.0001) after 24 h of exposure to predation, compared with that of the control. The dynamic changes in the signal transductions appeared to bring about new connections in the neural networks, as suggested by the microtubule dynamics. These connections may result in improved memory and cognition abilities, and subsequently increase survivability.